(3QSGdI aj MaX GdUMIs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3gPg QSGdI ai MaX GdUMI ddTjN GdQFjS QMeg Gddg , HYO GdOHGLI fbhd (B: (3GdHGH GdChd , ai PcQ GdcjajGJ s
(3BNQgG (B:s
(3hai dYH GdTWQfL hGdfQO , ef GdLgI GdJi jchf GdbeQ ai Jdc GdLgI EP bO HdZfG gPG GdeHdZ s
(3fSNI KGfjI MOjKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
Keywords: (3GdWHs